AN EMPIRICAL ANALYSIS OF LEADERSHIP STYLE, WORK DISCIPLINE, AND JOB SATISFACTION AMONG POLICE PERSONNEL - Benyamin Lufpi; Diah Rani Nartasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This literature review article examines the empirical relationships between leadership style, work discipline, and job satisfaction among police personnel. Law enforcement organizations operate in complex, high-risk environments where leadership quality, behavioral discipline, and psychological well-being of officers significantly shape organizational effectiveness and service quality. Drawing on empirical studies published between 2015 and 2025, this review synthesizes findings from policing and public-sector contexts to identify dominant leadership styles, disciplinary mechanisms, and job satisfaction determinants within police institutions. The review follows a structured literature review methodology, involving systematic identification, screening, and narrative synthesis of peer-reviewed journal articles and institutional studies. The findings reveal consistent evidence that transformational and ethical leadership styles positively influence work discipline and job satisfaction, while authoritarian or rigid leadership approaches often generate compliance without sustained satisfaction. Work discipline emerges as both an outcome of leadership practices and a mediating factor influencing job satisfaction and performance. Job satisfaction is found to be shaped by leadership fairness, organizational justice, workload management, and career development opportunities. The synthesis further highlights contextual moderators such as organizational culture, hierarchical structures, and public accountability pressures. This review contributes to the literature by integrating leadership, discipline, and satisfaction into a unified analytical framework specific to policing. The article concludes by emphasizing the need for leadership development strategies that balance authority and support, promote internal discipline through fairness rather than coercion, and enhance job satisfaction to sustain professional policing performance.